EVALUATING GENDER-BIAS IN THE IRANIAN PRE-UNIVERSITY ENGLISH TEXTBOOKS - Roohani, Ali; Zarei, Mandani (Indonesian Journal of Applied Linguistics, 2013)
Abstract: Textbooks can affect learners’ attitudes, viewpoints, and their choice of language in second/foreign language (L2) communication. The various ways in which the people are displayed in communication may affect students’ viewpoints. This study was an attempt to examine several potential areas of gender-bias in the representation of women and men in the pre-university English textbook, an English language teaching (ELT) textbook with two volumes taught in the high schools of Iran. To evaluate this textbook, content analysis was done in terms of gender-bias, gender-neutral, male-generics, and the firstness in the reading texts, instructions, exercises and illustrations. The frequency and percentages of names, nouns, pronouns and pictures attributed to each gender (i.e., males and females) were obtained and chi-square tests were carried out. In general, names, nouns and pictures pertinent to males outnumbered those attributed to females. Besides, there was a statistically significant difference between males and females in the two volumes of the pre-university textbook in terms of the above features. Also, male-oriented terms came first more frequently. However, there was not a statistically significant difference between male and female pronouns between the two volumes, though the percentage of male pronouns was higher. Moreover, the textbook included many gender-neutral nouns and pronouns not having any gender orientations. Findings indicated that the Iranian pre-university English textbook was somehow male-oriented and gender-biased as regards names, nouns, firstness and pictures associated with them though great efforts were made to avoid specific gender orientations.